2002
DOI: 10.1111/j.1749-6632.2002.tb04078.x
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAP Kinase Is Involved in Lipopolysaccharide‐Induced Dopaminergic Neuronal Cell Death in Rat Mesencephalic Neuron‐Glia Cultures

Abstract: Immune stimulants, such as the bacterial endotoxin, lipopolysaccharide (LPS), the human immunodeficiency virus-1 coat protein gp120, or beta-amyloid peptides, lead to glial activation and production of various immune mediators, such as nitric oxide (NO) and proinflammatory cytokines in the brain. These mediators appear to contribute to neuronal cell death in neurodegenerative diseases. However, the signaling pathways, which mediate the neurotoxic effect by the endotoxin, are not understood. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 58 publications
6
41
0
1
Order By: Relevance
“…[21][22][23] Our previous study showed that JNK signaling plays a major role in the regulation of LPS-stimulated NO produc- tion and iNOS expression, and regulatory effect of the JNK signaling pathway on NO production was dependent on cellular ROS. 16) In the present study, compound #4 treatment significantly inhibited the NO production and iNOS expression, as well as ROS.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Our previous study showed that JNK signaling plays a major role in the regulation of LPS-stimulated NO produc- tion and iNOS expression, and regulatory effect of the JNK signaling pathway on NO production was dependent on cellular ROS. 16) In the present study, compound #4 treatment significantly inhibited the NO production and iNOS expression, as well as ROS.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that TNF-␣ in conjunction with IFN-␥ produced neurotoxicity in neuron-glia cultures (57) and that inhibition of iNOS activity and NO production prevents LPS-induced neurotoxicity, indicating that NO production is also involved in LPSinduced neurodegeneration (58). Moreover, we recently found that a systemic injection of TNF-␣ can cause neuronal death (59) and the production of superoxide (L. Qin and J.-S. Hong, unpublished observations) in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, neuronal p38, not JNK, has been reported (Ciesielski-Treska et al, 2001) to play a significant role in mediating neuron death induced by chromogranin A-activated microglia. In a study of rat mesencephalic glia-neuron co-cultures (Jeohn et al, 2002), it was reported that p38 of the glia, not of the neurons, is involved in LPS-induced dopaminergic neuron death. The MEK-ERK pathway in microglia has been found (Combs et al, 1999) to be important in mediating the neurotoxic effects of ␤-amyloid-stimulated microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Our results in the present study showing that conditioned medium from activated glia does not induce neuron death are consistent with the neurotoxic substance(s) being short-lived, such as NO. In addition, there have been several studies linking MAPK activation with NO generation (Chan and Riches, 2001;Han et al, 2002;Jeohn et al, 2002;Park et al, 2002). However, our analysis of the ability of the MAPK inhibitors to suppress NO production in the glia-neuron co-culture reveals a more complicated scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation